Proceedings of the 8th ACM Conference on Designing Interactive Systems 2010
DOI: 10.1145/1858171.1858191
|View full text |Cite
|
Sign up to set email alerts
|

Coffee maker patterns and the design of energy feedback artefacts

Abstract: Smart electricity meters and home displays are being installed in people's homes with the assumption that households will make the necessary efforts to reduce their electricity consumption. However, present solutions do not sufficiently account for the social implications of design. There is a potential for greater savings if we can better understand how such designs affect behaviour. In this paper, we describe our design of an energy awareness artefact-the Energy AWARE Clock-and discuss it in relation to beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 11 publications
2
46
0
Order By: Relevance
“…Similarly to Broms et al [2] and Karapanos et al [11], we observed two phases in families' interactions with the eco-feedback interface: an initial orientation phase that lasted approximately 4 weeks, and after which we saw a decline of about 40% in users' interactions, followed by an incorporation phase which signified, first, the loss of the powermeter's novelty, and secondly its appropriation in families' daily routines. In the remainder of the paper we describe our findings with regard to our two research questions:…”
Section: Resultssupporting
confidence: 85%
“…Similarly to Broms et al [2] and Karapanos et al [11], we observed two phases in families' interactions with the eco-feedback interface: an initial orientation phase that lasted approximately 4 weeks, and after which we saw a decline of about 40% in users' interactions, followed by an incorporation phase which signified, first, the loss of the powermeter's novelty, and secondly its appropriation in families' daily routines. In the remainder of the paper we describe our findings with regard to our two research questions:…”
Section: Resultssupporting
confidence: 85%
“…The ease of measurement of, for example, electricity use has been integrated into interaction design in different forms of feedback with the aim of visualizing to users what is otherwise hidden e.g. [18][19][20][21][22]. However, most of the solutions developed in this field communicate through vision and a few involve other senses.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, empirical evidence is being reported through studies that investigate the effectiveness of; alternative forms of eco-feedback such as ambient feedback display (e.g. Broms et al, 2010;Kim et al, 2010); frequency of information displayed (Fitzpatrick and Smith, 2009;Hargreaves, 2010); and using online eco-feedback systems (Selvefors et al, 2013).…”
Section: Design For Sustainable Energy Consumptionmentioning
confidence: 99%